Human papillomavirus type 16 DNA cooperates with activated ras in transforming primary cells. - Matlashewski, G (1987)
The close association of human papillomavirus type 16 DNA with a majority of cervical carcinomas implies some role for the virus in this type of cancer. To define the transforming properties of HPV-16 DNA in vitro we have now performed transfection experiments on baby rat kidney cells using HPV-16 DNA in conjunction with an activated ras gene. We have demonstrated that a 6.6-kb DNA fragment, containing the early genes of HPV-16 under the control of Moloney murine leukaemia virus long terminal repeats (MoMuLV-LTRs), cooperates with EJ-ras in transforming these cells. Both DNAs are required and neither alone is effective. The cooperating activity appears to reside in a protein or proteins derived from the E6/E7 region of the HPV-16 genome.